2020
DOI: 10.1016/j.jhin.2020.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Inferring super-spreading from transmission clusters of COVID-19 in Hong Kong, Japan, and Singapore

Abstract: Super-spreading events in an outbreak can change the nature of an epidemic. Therefore, it is useful for public health teams to determine whether an ongoing outbreak has any contribution from such events, which may be amenable to interventions. We estimated the basic reproductive number (R 0 ) and the dispersion factor (k) from empirical data on clusters of epidemiologically linked coronavirus disease 2019 (COVID-19) cases in Hong Kong, Japan and Singapore. This allowed us to infer the presence or absence of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 11 publications
(14 reference statements)
8
41
0
Order By: Relevance
“…The pattern of superspreading events may however vary between outbreaks, and superspreaders could be unidentified or identified only after the event. An analysis of epidemiological data of 101 cases collected early in the epidemic as of 3 March 2020 in Hong Kong, Japan and Singapore suggested transmission was not overdispersed and did not find strong evidence for the presence of superspreading events [9] . However subsequent studies including one done in Hong Kong analysing 1,037 cases as of 28 April showed substantial individual heterogeneity in transmissibility ( k = 0·45, 95%; 0·3-0·72) [10] .…”
Section: Introductionmentioning
confidence: 97%
“…The pattern of superspreading events may however vary between outbreaks, and superspreaders could be unidentified or identified only after the event. An analysis of epidemiological data of 101 cases collected early in the epidemic as of 3 March 2020 in Hong Kong, Japan and Singapore suggested transmission was not overdispersed and did not find strong evidence for the presence of superspreading events [9] . However subsequent studies including one done in Hong Kong analysing 1,037 cases as of 28 April showed substantial individual heterogeneity in transmissibility ( k = 0·45, 95%; 0·3-0·72) [10] .…”
Section: Introductionmentioning
confidence: 97%
“…Such differences cannot be explained only by the policy designed by the government in power and the values on which it bases its decisions, when weighing between, let's say, human lives vs. economy, individual freedom vs. common good, or democracy vs. efficiency. There is a range of other factors to be taken into account, such as the initial conditions and early development of the outbreak of the disease as it unfolds, the global and regional connectedness of the country especially regarding the connections with the birthplace of the virus, COVID-19 epicenters or superspreading events (Frieden & Lee, 2020;Kwok et al, 2020), and the national and local cultures that affect the spread of the virus through customs, the patterns of social interaction and norm compliance. In addition, this is a rapidly changing phenomenon, which due to accidents or the behavior of a few individuals may provide surprises even to countries that have prepared well for these kinds of crises.…”
Section: Strategic Government Responsesmentioning
confidence: 99%
“…This likelihood is underscored by evidence indicating that COVID-19 spreads readily via asymptomatic 8 and airborne transmission 9 and superspreader events. 10 Recent tropical cyclones that have made landfall on island-based populations and coastal populations illustrate the dangers inherent in these intersecting challenges.…”
Section: Superimposed Threats To Population Health From Tropical Cyclmentioning
confidence: 99%